Gender differences in business travel: Implications for hotel and destination management - Ángel MILLÁN; M. Luisa FANJUL; Marta RETAMOSA (Tourism and Hospitality Management)
Purpose – The aim of this study is to investigate the influence of gender differences on the evaluation of hotels and destination attributes with regard to business travel. Methodology/Design/Approach – This research employs a cross-sectional questionnaire survey and a sample of 318 business travellers. The analysis methods used are descriptive, such as a t-test, frequency distribution, cross tabulation and a chi-square analysis. Findings – The findings reveal significant differences when evaluating the attributes of hotels and destinations. Certain hotel attributes are rated at a significantly higher level by women than by men. Female respondents attained higher mean scores for all the destination attributes. Previous studies have attained very little knowledge in terms of understanding how gender works as regards differentiating business travellers’ behaviour. Originality of the research – The results support the hypothesis that gender influences the evaluation of hotel services and destinations. These findings may have significant implications for service innovation and positioning strategies in the business travel industry.